Selling by Numbers: The Quantification and Marketization of the Swedish Art World for Contemporary Art - Wikberg, Erik; Strannegard, Lars (Organizational Aesthetics, 2014)
This article describes and analyzes the role of market practices and its impact on the organization of the Swedish Art world between 1981 and 2011. Drawing on a sprawling set of empirical data, we show how the Swedish Art world for contemporary art has had an increasing number of market places of different types, and how these are culturally infused with values and narratives. We propose that the re-organization of the Swedish Art world for contemporary art can be summarized in three new orders: 1) in a move towards the ideal type of a market, 2) in a turn towards quantification and commensuration, and 3) in the organization of new market places as a reaction to marketization.